HUBUNGAN SELF-EFFICACY DAN EMOTIONAL INTELLIGENCE DENGAN PRESTASI BELAJAR MATEMATIKA SISWA SMA NEGERI 6 BALIKPAPAN - Mawar Zakia Warsi; Rahayu Sri Waskitoningtyas; Nur Ismiyati (EMTEKA: Jurnal Pendidikan Matematika, 2022)
This study aims to examine the relationship between self-efficacy and emotional intelligence with student achievement in mathematics. This type of research is correlation research. The research population is SMA Negeri 6 Balikpapan students for the 2021/2022 academic year. Sampling in class XII IPA was carried out using cluster random sampling technique. The sample in this study amounted to 123 students. Data collection techniques in this study are questionnaires and documentation. The research data collected was then analyzed using the product moment correlation test and multiple correlation analysis. The results of data analysis showed that there was a significant relationship between self-efficacy and student achievement in mathematics, with the correlation coefficient r=0.414 or the level of the relationship was classified as moderate. Furthermore, it was found that there was a significant relationship between emotional intelligence and students' mathematics learning achievement, with a correlation coefficient value of r=0.312 or the level of the relationship was classified as weak. In addition, the results of data analysis also show that together, there is a significant relationship between self-efficacy and emotional intelligence with students' mathematics learning achievement, with a correlation coefficient of r=0.430 or a moderate level of relationship.